2002
DOI: 10.1038/sj.npp.1300112
|View full text |Cite|
|
Sign up to set email alerts
|

Post-mortem Interval Effects on the Phosphorylation of Signaling Proteins

Abstract: Post-mortem brain tissue provides a unique opportunity to uncover the genes or proteins involved in the pathophysiology of neuropsychiatric disorders. Protein phosphorylation is a common protein modification within intracellular signaling pathways that affects the distribution and function of protein, and has been hypothesized to be of major importance in both the pathophysiology and treatment of major neuropsychiatric disorders. Thus, we were interested in ascertaining the stability of the phosphorylated form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 59 publications
1
69
0
Order By: Relevance
“…Postmortem variables such as PMI may also impact phosphorylation (Funk et al, 2012;Li et al, 1996Li et al, , 2003Li et al, , 2005O'Callaghan and Sriram, 2004;Oka et al, 2011). The often transient nature of phosphorylation is well characterized, and in part led to the development of strategies (such as microwave devices) for rapid 'fixation' of brain tissues particularly for proteins with a rapid turnover cycle for phosphorylation/dephosphorylation (O'Callaghan and Sriram, 2004).…”
Section: Biochemical Assessment Of Post-translational Modification Inmentioning
confidence: 99%
“…Postmortem variables such as PMI may also impact phosphorylation (Funk et al, 2012;Li et al, 1996Li et al, , 2003Li et al, , 2005O'Callaghan and Sriram, 2004;Oka et al, 2011). The often transient nature of phosphorylation is well characterized, and in part led to the development of strategies (such as microwave devices) for rapid 'fixation' of brain tissues particularly for proteins with a rapid turnover cycle for phosphorylation/dephosphorylation (O'Callaghan and Sriram, 2004).…”
Section: Biochemical Assessment Of Post-translational Modification Inmentioning
confidence: 99%
“…We did not, however, observe a significant increase in pATF2 in nonmedicated depressed patients compared to normal controls. Li et al (2003) have recently shown that postmortem interval (PMI) produces profound and relatively rapid effects on the phosphorylation of proteins involved in intracellular signaling, including specifically the phosphorylation of ATF2. The inclusion of PMI as a covariate in our model did not result in a significant effect, indicating that differences in PMI between groups could not account for the lack of effect observed.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of the usual 2-DE based approach therefore clearly influence the degradome data, making it tempting to define these results as "2-DEgradomes." It should also be noticed that the PMI PTM knowledge is mainly based on protein phosphorylation, with different proteins displaying varying levels of PMI sensitivity within the first 10h (1,3,9,17) but there are also reports on PMI sensitivity among acetylated lysines (9). The more proteolytic nature of the pancreas is probably responsible for the fact that ϳ99% of the liver proteome is similar between D and FD whereas this is only the case for ϳ89% in pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Post mortem degradation in during PMI is a well known compromising problem when studying endogenous peptides (2,3) and has also been proven to affect the results of polypeptide (here defined as proteins larger than 10 kDa) studies (3)(4)(5)(6)(7)(8). PMI degradation has mainly been studied on human or mouse brain tissue, using two-dimensional electrophoresis (2-DE), SDS-PAGE, and immunoblotting (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). There are also a few proteomic studies on muscle tissue degradation in livestock (13)(14)(15)(16).…”
mentioning
confidence: 99%